2014
DOI: 10.1007/s10867-014-9348-x
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic investigation of the interaction between c-MYC DNA and tetrapyridinoporphyrazinatozinc(II)

Abstract: The c-MYC gene plays an important role in the regulation of cell proliferation and growth and it is overexpressed in a wide variety of human cancers. Around 90% of c-MYC transcription is controlled by the nuclease-hypersensitive element III1 (NHE III1), whose 27-nt purine-rich strand has the ability to form a G-quadruplex structure under physiological conditions. Therefore, c-MYC DNA is an attractive target for drug design, especially for cancer chemotherapy. Here, the interaction of water-soluble tetrapyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The current growing interest in the G4 DNA structures of promoter regions [90,91], in particular versus c-myc , led us to analyze the docking poses obtained on h-telo and c-myc receptors. With the aim to highlight the differences in the recognition of the used DNA G4 folds, we performed a contact analysis evaluating the interactions in terms of hydrogen bonds and Van der Waal’s contacts by means of Maestro graphical interface (Maestro Graphics User Interface, ver.…”
Section: Resultsmentioning
confidence: 99%
“…The current growing interest in the G4 DNA structures of promoter regions [90,91], in particular versus c-myc , led us to analyze the docking poses obtained on h-telo and c-myc receptors. With the aim to highlight the differences in the recognition of the used DNA G4 folds, we performed a contact analysis evaluating the interactions in terms of hydrogen bonds and Van der Waal’s contacts by means of Maestro graphical interface (Maestro Graphics User Interface, ver.…”
Section: Resultsmentioning
confidence: 99%
“…5 Recent studies showed that the G-rich promoter of the cmyc oncogene can form a G-quadruplex structure via a Hoogesten hydrogen bond in the presence of K + and Na + ions. 6 Complexes that can bind and stabilize G-quadruplex DNA usually exhibit excellent inhibitory activity against the growth of tumor cells. For example, porphyrin and quindoline inhibit various tumor cells by stabilizing the c-myc G-quadruplex DNA.…”
Section: ■ Introductionmentioning
confidence: 97%
“…The in vitro and in vivo inhibitory activities of these complexes, as well as their underlying mechanisms and binding behavior to DNA molecules, have been extensively investigated. RAPTA-B ([Ru(η 6 -C 6 H 6 )(pta)-Cl 2 ]) and RAPTA-C ([Ru(η 6 -p-C 6 H 4 Me i Pr)(pta)Cl 2 ]) blocked tumor metastasis of a CBA mouse model for human breast cancer by preventing angiogenesis. 3 In addition, the arene Ru(II) complex RM175 ([(η 6 -biphenyl)Ru(ethylenediamine)-Cl] + ) inhibited tumor metastasis in vivo and blocked migration and invasion through enhancing cell−cell readhesion and down-regulated the matrix metalloproteinases (MMPs).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These derivatives are cationic phtalocyanines/porphyrazines [111,118,[126][127][128][129] or core-expanded porphyrins [130,131]. It is striking to note that negatively charged compounds such as Nmethylmesoporphyrin IX (NMM) [44,45,132,133], protoporphyrin IX [134], hemin (Fe IIIprotoporphyrin IX) [135][136][137] with two carboxylic groups or tetraphtalocyanines with four sulfonate groups [138][139][140] are endowed with G-quadruplex binding capability.…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 99%